2008
DOI: 10.1080/14767050701830514
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid prostaglandin concentrations increase before the onset of spontaneous labor at term

Abstract: Objectives. The role of prostaglandins (PGs) in the onset of human parturition has been controversial. Specifically, some investigators have proposed that PGs are the consequence rather than the cause of labor. An important question is whether or not amniotic fluid (AF) PG concentrations increase before the onset of labor in humans. Methods. The concentrations of PGs were determined in AF obtained from 167 singleton pregnant women with intact membranes. Patients were divided into four groups: (1) preterm not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 23 publications
2
47
1
2
Order By: Relevance
“…The coincidence between these findings and the timing of the PTL episodes, at a median age of 32.5 gestational weeks (interquartile range, 29.2-34.6 weeks), implicates rapid fetal growth rates as contributory. This is a novel observation, provoking consideration of fetal contributions to the mechanisms and biological cascade underlying the onset of labor (Challis et al, 2002;Lee et al, 2008). Two findings emerged in this study that differentiated the growth patterns of these fetuses: (1) A three-phase growth phenotype characterized by two times of faster growth separated by an interval of slow-down in AC growth; (2) an abdominal growth perturbation that accompanied differences in proportionality and allometry.…”
Section: Discussionmentioning
confidence: 90%
“…The coincidence between these findings and the timing of the PTL episodes, at a median age of 32.5 gestational weeks (interquartile range, 29.2-34.6 weeks), implicates rapid fetal growth rates as contributory. This is a novel observation, provoking consideration of fetal contributions to the mechanisms and biological cascade underlying the onset of labor (Challis et al, 2002;Lee et al, 2008). Two findings emerged in this study that differentiated the growth patterns of these fetuses: (1) A three-phase growth phenotype characterized by two times of faster growth separated by an interval of slow-down in AC growth; (2) an abdominal growth perturbation that accompanied differences in proportionality and allometry.…”
Section: Discussionmentioning
confidence: 90%
“…An elevated amniotic fluid PGF 2α concentration was defined as ≥170 pg/mL. This is based on our previous study which reported that an amniotic fluid PGF 2α concentration of 170 pg/mL corresponded to the value at the 95th percentile for pregnant women with intact membranes at 15–36 weeks of gestation who were not in labor [142]. …”
Section: Methodsmentioning
confidence: 99%
“…The main prostaglandins found in amniotic fluid are prostaglandin E 2 (PGE 2 ) and prostaglandin F 2α (PGF 2α ) [142, 178, 179]. The concentration of these eicosanoids increases prior to the onset of labor at term [136, 140, 142], during labor [133, 179] and rupture of the membranes [132], and in spontaneous preterm labor [particularly in the setting of microbial invasion of the amniotic cavity (MIAC)] [129131, 137, 173, 180187].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of proinflammatory cytokines and uterotonic agents known to be involved in the onset of labor were also examined in terms of the enzymes in human amniotic cells. TNFa, IL1b, and IL6 [13] as well as prostaglandin F2a (PGF2a) [14] are increased in amniotic fluid with labor at term, and they are increased in maternal serum before labor onset [15]. IL8 is induced by IL1b [16].…”
Section: Introductionmentioning
confidence: 98%